Recontextualización del principio de conservación de la energía a través de la teoría de sistemas - Gallego Quiceno, Dany Esteban (Revista Científica, 2011)
In the context of physics education covers various topics related to the principle of conservation of energy that conceptual and procedural show where people referring to work, heat and temperature. This will also encourage the confusion of concepts, reflects a particular way of taking the process of formalizing their relationship with the organization of physical phenomena in such processes is reduced to formalize the use of algorithms and mathematical symbols. Looking for alternative routes to teaching thermodynamic phenomena, this research is developed from a historical-epistemological reflection of PCE based on systems theory, is a historical analysis of how epistemological as Newton, Mayer, Helmholtz, Robert Boyle, Joseph Black, formalize these concepts, so are recontextualized and formalized in the context of education. Shown with this analysis as the redefinition of the principle allows for a better understanding of the thermodynamic phenomena in students of college and high school level.